Evaluación de inmunoglobulinas (g y m) en el tratamiento de piodermas en perros domésticos (canis lupus familiaris) mediante el uso de apitoxina natural. - Yépez von Maack, Teresa Rebeca (Ecuador: Latacunga: Universidad Técnica de Cotopaxi (UTC)., 2020)
The objective of this project is to evaluate the immunomodulatory effect of apitoxin by bee (appis melífera) sting, as an adjunctive treatment in pyoderma of domestic canines (cannis lupus familiaris) providing balance to the immune system of dogs. 15 dogs of different race, age and sex were use, a sample of the affected area of the skin was taken for analysis in the laboratory, after checking the existence of pyoderma, a blood sample was taken from each dog before starting the treatment, the first analysis was carried out before the procedure began, 5 dogs were taken as a control in which only the bath were aplied, another 5 dogs were treated with the number 1 treatment with direct inoculation of apitoxin each 24 hours and the remaining 5 dogs were applied treatment number 2 with direct inoculation every 48 hours, both were applied in the ventral area, to the sides of the alba line and below the navel, in small dogs it was applied 3 pickets and in medium and large 6 for 3 sessions, after 15 and 21 days a new blood sample was taken to determine the values of IgG and IgM. The treatment was accompanied with a bath for 3 occasions every 4 days with a chlorhexidine-based shampoo. 250 mg, 15 mg / kg cephalexin was used every 8 hours for 14 days in group 1 and 2. Using a descriptive DCA statistic and a 1% Tukey test, it was determined that the immunostimulatory effect of apitoxin on IgG and IgM presents a favorable change at 21 days using apitoxin every 24 hours, with a mean of (8.8 ± 0.86) in IgG and a mean of (1.41 ± 0.18) in IgM, showing that both IgG and IgM are maintained within the ranges considered IgG (5-17 g / L) and IgM (0.7-2.7 g / L), consequently in the presented tables an increase in both immunoglobulins could be evidenced starting from day 0, passing by day 15 until day 21, it is demonstrated that all dogs showed variation within normal immunological ranges. The treatment was favorable for animals, showing that the use of apitoxin as an adjuvant for the treatment of pyoderma has a positive effect. It ...